2014
DOI: 10.1099/ijs.0.052548-0
|View full text |Cite|
|
Sign up to set email alerts
|

Kocuria indica sp. nov., isolated from a sediment sample

Abstract: An actinobacterial strain was isolated from a sediment sample from Chorao Island, in Goa province, India, and subjected to a taxonomic investigation. The isolate, designated NIO-1021 T , was a Gram-stain positive, aerobic, non-motile and coccoid. Strain NIO-1021 T was identified as a member of the genus Kocuria by a polyphasic approach. Strain NIO-1021 T could be differentiated from other members of the genus Kocuria on the basis of physiology and 16S rRNA gene sequence analysis. The 16S rRNA gene sequence sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The description is as before (Dastager et al, 2014c ) with the following modification. The G+C content of the type-strain genome is 68.9%, its approximate size 2.88 Mbp, its GenBank deposit SAMN06296028 .…”
Section: Discussionmentioning
confidence: 99%
“…The description is as before (Dastager et al, 2014c ) with the following modification. The G+C content of the type-strain genome is 68.9%, its approximate size 2.88 Mbp, its GenBank deposit SAMN06296028 .…”
Section: Discussionmentioning
confidence: 99%
“…The genome sequences of K. flava HO-9041 from inland air, Kocuria sp. SM24M-10 from the mucus of the coral Mussismilia hispida ( Palermo et al, 2016 ), K. indica DSM 25126 from a marine sediment sample ( Dastager et al, 2014 ), K. rhizophila P7-4 from the intestine of the fish Siganus doliatus ( Kim et al, 2011 ) and K. rhizophila DC2201 from a soil sample ( Takarada et al, 2008 ) were downloaded from NCBI 3 and served as the reference genomes for subsequent analysis. Genome alignment of K. flava S43 and K. flava HO-9041 was carried out using MAUVE software ( Darling et al, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…The genus Kocuria was established by Stackebrandt et al (1995) by taxonomic dissection of the genus Micrococcus , and was clearly separated from Micrococcus and Micrococcus -related taxa on the basis of phylogenetic analyses using 16S rRNA gene sequences. At the time of writing (November 2014), the genus Kocuria , contains 19 species with validly published names including Kocuria kristinae , Kocuria rosea and Kocuria varians (Stackebrandt et al , 1995), Kocuria erythromyxa (Rainey et al , 1997; later reclassified as a later synonym of K. rosea ), Kocuria palustris , Kocuria rhizophila (Kovács et al , 1999), Kocuria polaris (Reddy et al , 2003), Kocuria marina (Kim et al , 2004), Kocuria carniphila (Tvrzová et al , 2005), Kocuria aegyptia (Li et al , 2006), Kocuria himachalensis (Mayilraj et al , 2006), Kocuria flava , Kocuria turfanensis (Zhou et al , 2008), Kocuria halotolerans (Tang et al , 2009), Kocuria atrinae (Park et al , 2010a), Kocuria koreensis (Park et al , 2010b), Kocuria gwangalliensis (Seo et al , 2009), Kocuria salsicia (Yun et al , 2011) and Kocuria indica (Dastager et al , 2014). During our study on the microbial diversity and taxonomy of the halotolerant and halophilic bacteria from saline and alkaline soils in the Songnen Plain (Pan et al , 2012), an actinobacterium, designated NEAU-ST5-33 T , was shown to share a 16S rRNA gene sequence similarity of 98.8 % with K. polaris CMS 76or T and K. rosea DMS 20447 T , suggesting that strain NEAU-ST5-33 T may represent a novel taxon.…”
mentioning
confidence: 99%